Current status and future directions of demostic surgical robots - Cao Peng; Wang Guohui; Yi Bo; Zhu Shaihong (结直肠肛门外科)
With the rapid development of medical technology, surgical robots, as one of the cutting-edge technology, has received widespread attention. This article aims to explore the current status and future directions of demostic surgical robots, firstly review the development history of demostic surgical robots and summarize the current main application areas and technical characteristics, and then highlight the important achievements and breakthroughs of demostic surgical robots, and finally analyze the development trends of the demostic surgical robots industry and discuss the directions for technological improvement and innovation.